2021
DOI: 10.1002/fsn3.2377
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial composition and function during fermentation of Mongolia koumiss

Abstract: Koumiss, also called Airag, or Chige is a spontaneously fermented mares' milk beverage that is very popular in Central Asia; it is thought to be of Huno-Bulgar, Turkic and Mongol origin and has been drunk habitually since ancient times (Sudun et al., 2013). Koumiss can be mildly alcoholic, but would need to be consumed in enormous quantities to have any noticeable effects (Bakir et al.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 42 publications
(54 reference statements)
1
9
0
Order By: Relevance
“…The studies available on qymyz revealed that the main microorganisms responsible for the fermentation were lactic acid bacteria (LAB) and yeasts [4]. The authors mainly focused on the identification of microorganisms [3,5,6]. Rakhmanova et al [3] found 52 lactic acid bacteria and 20 yeasts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The studies available on qymyz revealed that the main microorganisms responsible for the fermentation were lactic acid bacteria (LAB) and yeasts [4]. The authors mainly focused on the identification of microorganisms [3,5,6]. Rakhmanova et al [3] found 52 lactic acid bacteria and 20 yeasts.…”
Section: Introductionmentioning
confidence: 99%
“…Rakhmanova et al [3] found 52 lactic acid bacteria and 20 yeasts. Wu et al [5] stated that LAB played a major role in the sanitary quality of qymyz by decreasing the pH. Yeasts in qymyz produce ethanol and could contribute to production of its typical aroma [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Koumiss consumption caused significant changes in metabolites involving in numerous metabolic pathway, including biosynthesis of primary and secondary bile acid, as well as metabolism of unsaturated fatty acid, linoleic acid and arachidonic acid ( 44 ). The study also demonstrated that koumiss was related to fat synthesis and metabolism ( 18 ), which might be another important impact factor against T. gondii infection.…”
Section: Discussionmentioning
confidence: 90%
“…Moreover, koumiss has more essential fatty acids than milk, which is good for human health (17). The ratio of casein to whey is 1:1 in koumiss, which is close to that in human milk (18). In addition to its high nutritional value, koumiss also has excellent therapeutic potential due to its anticarcinogenic and antioxidative properties, antibacterial properties and intestinal enlargement (16).…”
Section: Introductionmentioning
confidence: 94%
“…The protein composition in Koumiss is 1.7%–2.2% and is based on the milk origin. The ratio of casein to whey is 1:1 near human milk (Ha et al., 2003 ; Wu et al., 2021 ).…”
Section: Nutritional Compositionmentioning
confidence: 99%